2022
DOI: 10.1007/s00436-022-07571-y
|View full text |Cite
|
Sign up to set email alerts
|

Activity of isoflavone biochanin A in chronic experimental toxoplasmosis: impact on inflammation

Abstract: Toxoplasma gondii is a worldwide prevalent parasite. The infection has been linked to variable inflammatory effects including neuroinflammation. Biochanin A (BCA) is an isoflavone, known for its anti-inflammatory and anti-oxidative properties. In this study, we examined the effect of BCA on the brain and liver inflammatory lesions in a murine model with chronic toxoplasmosis. Mice were divided in to six groups: non-infected control, non-infected BCA-treated, and four infected groups with Toxoplasmagondii Me49-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Several lncRNAs and mRNAs have been identified to be differentially expressed in the liver during the course of infection with T. gondii [ 2 , 5 ]. For example, a study found that the mRNA for the pro-inflammatory cytokine TNF-α was significantly upregulated in T. gondii -infected livers [ 6 ]. TNF-α is known to promote liver inflammation and can contribute to liver damage [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several lncRNAs and mRNAs have been identified to be differentially expressed in the liver during the course of infection with T. gondii [ 2 , 5 ]. For example, a study found that the mRNA for the pro-inflammatory cytokine TNF-α was significantly upregulated in T. gondii -infected livers [ 6 ]. TNF-α is known to promote liver inflammation and can contribute to liver damage [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…One compound, BSI-066, is an isoflavone named biochanin A, which has been reported to possess phytoestrogenic activity [ 35 ] and regulate inflammation [ 36 , 37 ]. Isoflavones have been reported to suppress cancer growth [ 38 , 39 ] and inhibit some viral infections as detailed below.…”
Section: Discussionmentioning
confidence: 99%
“…Positive control, or the Li 2 CO 3 group, consisted of rats that received 24 mg/kg Li 2 CO 3 by oral gavage every alternate day for 7 weeks to induce renal injury. (17) Li 2 CO 3 and BCA therapeutic group (Li 2 CO 3 + BCA) consisted of rats received 24 mg/kg Li 2 CO 3 orally every alternate day for 7 weeks, then receive 50 mg/kg BCA orally daily for 3 weeks (18). BCA and Li 2 CO 3 protective group (BCA+ Li 2 CO 3 ) consisted of rats received 50 mg/kg BCA orally at same time with 24 mg/kg Li 2 CO 3 every alternate day for 7 weeks.…”
Section: Animal Interventionmentioning
confidence: 99%
“…BCA and Li 2 CO 3 protective group (BCA+ Li 2 CO 3 ) consisted of rats received 50 mg/kg BCA orally at same time with 24 mg/kg Li 2 CO 3 every alternate day for 7 weeks. (18) Total body weights of rats estimated at beginning and end of experimental using digital scale. At 7 th weeks, followed 12 hours of experimental end, rats anesthetized by inhalation of diethyl ether.…”
Section: Animal Interventionmentioning
confidence: 99%